Opportunistic screening for atrial fibrillation in a rural area. Issue 8 (27th January 2016) - Smyth, B.; Marsden, P.; Corcoran, R.; Walsh, R.; Brennan, C.; McSharry, K.; Clarke, J.; Kelly, P.J.; Harbison, J.
Abstract : Introduction: Opportunistic screening is an effective means of identifying subjects with Atrial Fibrillation (AF). Previous studies of opportunistic screening have been performed areas with high population density and before the development of novel oral anticoagulant drugs. We performed a study to determine feasibility of AF screening in a predominantly rural, low population density area. Methods: Over 6 months, subjects 65 years and older were screened by local General Practitioners using radial pulse palpation confirmed by 12 lead Electrocardiogram. Data were recorded electronically and those with newly identified AF were followed up to examine management post diagnosis. Results: In total, 7262 subjects were screened and an irregular pulse was found in 916 (12.6%) of whom 735 (10.1%) had known AF and 55 (0.76%) had newly detected AF. Of these 55 patients with newly documented AF, 28 (50.9%) were women, 38 (69.1%) had hypertension and eight (14.5%) had a smoking history. Mean body mass index in subjects with newly documented AF was 28.9 kg/m 2 (SD 5.6) There was no significant difference in gender mix ( P =  0.4), smoking history ( P  =  0.8) or alcohol history ( P   =  0.8) with the overall population. Fifty-one (92.7%) subjects had a CHA2DS2VaSC score  ≥ 2 of whom 33 (64.7%) were eventually anticoagulated and nine (17.6%) commenced on Aspirin. The rate of newly identified patients in AF was lower than in previous reported key studies because of a higher rate of subjects with known AF. Conclusion: Opportunistic AF screening in a rural environment identified a substantial number of new cases, although less than in previous screening studies.